Semi‐Locked Tetrathienylethene as a Building Block for Hole‐Transporting Materials: Toward Efficient and Stable Perovskite Solar Cells. (18th February 2019) - Shen, Chao; Wu, Yongzhen; Zhang, Hao; Li, Erpeng; Zhang, Weiwei; Xu, Xiaojia; Wu, Wenjun; Tian, He; Zhu, Wei‐Hong
Abstract: The construction of state‐of‐the‐art hole‐transporting materials (HTMs) is challenging regarding the appropriate molecular configuration for simultaneously achieving high morphology uniformity and charge mobility, especially because of the lack of appropriate building blocks. Herein a semi‐locked tetrathienylethene (TTE) serves as a promising building block for HTMs by fine‐tuning molecular planarity. Upon incorporation of four triphenylamine groups, the resulting TTE represents the first hybrid orthogonal and planar conformation, thus leading to the desirable electronic and morphological properties in perovskite solar cells (PSCs). Owing to its high hole mobility, deep lying HOMO level, and excellent thin film quality, the dopant‐free TTE‐based PSCs exhibit a very promising efficiency of over 20 % with long‐term stability, achieving to date the best performances among dopant‐free HTM‐based planar n‐i‐p structured PSCs. Abstract : Bausteine : Sterisch semifixiertes Tetrathienylethen (TTE), das eine hybride planare und orthogonale molekulare Konformation aufweist, wird als Strukturkern für den Aufbau von Lochtransportmaterialien (HTMs) eingeführt. Das resultierende TTE ermöglicht die beste Photovoltaikleistung unter den dotandfreien HTM‐basierten planaren Perowskitsolarzellen vom n‐i‐p‐Typ.